GAMMA-DELTA T CELLS MEDIATE ALPHA-BETA T CELL ACTIVATION IN ANGIOTENSIN II-INDUCED HYPERTENSION. (April 2021) - Caillon, Antoine; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Objective: Both innate and adaptive immune cells have been shown to play a role in hypertension and vascular injury. Recently, we demonstrated that a small subset of "innate-like" T lymphocytes, expressing the γδ T cell receptor (TCR) rather than the αβ TCR, plays a key role in hypertension and vascular injury. We demonstrated an increased number and activation (CD69+) of αβ and γδ T cells during the development of hypertension caused by angiotensin (Ang) II infusion, and that deficiency in γδ T cells prevented Ang II-induced hypertension, resistance artery endothelial dysfunction and spleen T-cell activation in mice. We hypothesized that γδ T cells mediate activation of other T cells in hypertension. Design and method: Fourteen to 15-week-old aged C57BL/6J male mice were infused or not with Ang II (490 ng/kg/min, SC) for 7 and 14 days (n = 5–7). γδ and αβ T cells were isolated from peripheral lymph nodes and spleen and αβ T cells were cultured alone or with γδ T cells (5:1) in presence of anti-CD3 antibodies plus or minus Ang II. T cell phenotype was evaluated by flow cytometry. Results: Close correlations were demonstrated between the number (#) of activated CD69 + γδ T cells and CD4 + CD69 + T cells (r2 = 0.74, P < 0.01) and CD8 + CD69 + T cells (r2 = 0.64, P < 0.01) after 7-day Ang II infusion. In vitro, Ang II increased the fraction of CD69 + αβ T cells when αβ T cells were co-cultured with γδ T cells isolated from control mice (% of αβ T cells: 19.9 ± 2.9 vs. 16.4 ± 2.6, P < 0.001) but not when cultured alone. The fractions of CD69 + (% of CD69 + αβ T cells: 35.7 ± 2.7 vs. 18.9 ± 1.5, P < 0.001) and CCR6 + αβ T cells (% of CCR6 + αβ T cells: 27.6 ± 2.4 vs. 19.2 ± 3.5, P < 0.05) were increased when αβ T cells were co-cultured with γδ T cells isolated from Ang II-infused compared to control mice. Conclusions: These results suggest that γδ T cells mediate activation of αβ T cells in Ang II-induced hypertension. Targeting γδ T cells may contribute to reduce the low-grade inflammation found in hypertension.